Hand preference across the lifespan: effects of end-goal, task nature, and object location - Gonzalez, Claudia L. R.; Flindall, Jason W.; Stone, Kayla D. (Frontiers in Psychology, 2015)
In the present study we investigate age-related changes in hand preference for grasping and the influence of task demands on such preference. Children (2-11), young-adults (17-28) and older-adults (57-90) were examined in a grasp-to-eat and a grasp-to-construct task. The end-goal of these tasks was different (eat versus construct) as was the nature of the task (unimanual versus bimanual). In both tasks, ipsilateral and contralateral grasps were analyzed. Results showed a right-hand preference that did not change with age. Across the three age groups, a more robust right-hand preference was observed for the unimanual, grasp-to-eat task. To disentangle if the nature (unimanual) or the end-goal (grasp-to-eat) was the driver of the robust right-hand preference, a follow up experiment was conducted. Young-adult participants completed a unimanual grasp-to-place task. This was contrasted with the unimanual grasp-to-eat task and the bimanual grasp-to-construct task. Rates of hand preference for the grasp-to-eat task remained the highest when compared to the other two grasping tasks. Together, the results demonstrate that hand preference remains stable from childhood to older adulthood, and they suggest that a left hemisphere specialization exists for grasping, particularly when bringing food to the mouth.